The Effect of Service Quality, Product Attractiveness, and Customer Experience on Repurchase Intention - Julianti, J; Hiong, Lauw Sun; Graceallah, Georgerius (Universitas Muhammadiyah Surakarta, 2025)
This study aims to determine the effect of Service Quality Product Attractiveness and Customer Experience on Repurchase Intention at Toss Cafe in Pontianak. This study uses a form of causal associative research with data collection techniques in the form of questionnaire distribution. The sampling technique used the quota sampling method with a sample size of 170 respondents. The data analysis technique used is the Stastical Package for Social Science (SPSS) version 23 analysis tool. Variable data testing in this study was carried out through validity test and reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test and hypothesis testing in the form of F test and t test. the results obtained in this study are that there is a positive and significant influence between Service Quality (X1), Product Attractiveness (X2), and Customer Experience (X3) on Repurchase Intention (Y) at Toss Cafe in Pontianak.